Hubungan Perawatan Botol Susu Dan Perilaku Mencuci Tangan Dengan Kejadian Diare Pada Batita Di Wilayah Kerja Puskesmas Delanggu - Sri Rahayu, Aysiyah; , Abi Muhlisin, SKM, M.Kep; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Diarrhea was still one of the major causes of morbidity and mortality in almost all geographic regions of the world and all age groups can be attacked by diarrhea. Diarrhea was a risk factor for behavioral factors such as the use of milk bottles were not clean. The rest of the milk in the bottle will be exposed to bacteria from saliva and mouth of a child less than three years. The aim of this study treatment relationship bottles and wash your hands and healthy behaviors in family structure with diarrhea in child under three years in Puskesmas Delanggu. This study was a retrospective descriptive correlative approach. Sample research was the mother and the child under three years were recorded in health centers Delanggu in September 2015 that as many as 142 respondents with a proportional random sampling technique. Collecting data using questionnaires were analyzed using Chi Square test. Conclusion of the study are (1) behavioral treatment bottle of milk in child under three years are mostly bad (45%), (2) hand washing mothers with child under three years majority were sufficient (51%), (3) there was a relationship behavioral treatments milk bottle with the incidence of diarrhea in child under three years in Puskesmas Delanggu where the better behavioral treatments milk bottle, the incidence of diarrhea was getting low, and (4) there was a relationship hand washing with diarrhea in child under three years in Puskesmas Delanggu where the better hand washing, the incidence of diarrhea lower. Keywords: nursing bottles, handwashing, diarrhea, child under three years